Spartan heart eaudiobook - Estep, Jennifer (Mythos Academy spinoff, 2019)
New school year, same old problems . . . At Mythos Academy, everyone knows exactly who I am: Rory Forseti, Spartan girl and the daughter of Reapers. Even though I fought alongside my cousin Gwen Frost to save the mythological world from Loki and his evil Reapers of Chaos, I'm still the most hated girl at the academy because of all the horrible things my parents did. I had hoped that this school year would be different, but the other kids just won't let me forget about my parents. But something strange is going on at the Colorado academy. First, I run into a Viking guy who dislikes me more than most. Then I notice some odd artifacts in the Library of Antiquities. And worst of all, I start hearing rumors about a new group of Reapers who can summon mythological monsters. I might be the most hated girl at Mythos Academy, but I'm also the only one who can save it . . .